Determinan Indeks Pembangunan Manusia dengan Pendekatan Maqasid Syariah Al-Ghazali - Bahtiar, Yusuf; Hannase, Mulawarman (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2021)
The purpose of this study is to determine what influences the Determinants of the Human Development Index in 5 Provinces of Eastern Indonesia. This study uses time series data and annual cross-sections during 2010-2018 in 5 provinces of Eastern Indonesia. Panel data analysis method with Fixed Effect Model (FEM) approach with Maqasid Syariah Al-Ghazali approach. The results of the study show that the ifẓ Nafs variable and the first ifẓ Māl variable have a negative effect on the Human Development Index in 5 Provinces of Eastern Indonesia. Meanwhile, the second element ifẓ 'Aql and ifẓ Māl variable have a positive and significant impact on the Human Development Index in 5 Provinces of Eastern Indonesia.